2022
DOI: 10.3390/su15010131
|View full text |Cite
|
Sign up to set email alerts
|

Ideologies, Conspiracy Beliefs, and the Chinese Public’s Politicized Attitudes to Climate Change

Abstract: While ideologies consistently influence public opinions on climate change in Western democracies, whether they affect the Chinese public’s climate attitudes is unknown. By applying a well-established measure of Chinese ideology, this study conducted a nationwide survey (n = 1469) on the relationships between climate attitudes and ideologies, conspiracy beliefs, and science literacy. It is the first study to empirically investigate the impact of ideological tendencies, conspiracy beliefs, and conspiratorial thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A meta-analysis of zero-order correlations has shown conspiracy mentality to be less strongly related to low cognitive ability (r = .20 for the BCTI, r = .09 for the CMQ; Stasielowicz, 2022). Furthermore, Pan et al (2023) observed that climate change denial was positively related to belief in conspiracy theories but negatively related to endorsement of conspiracy mentality statements. Taken together, these findings suggest that the greater empirical riskiness of belief in conspiracy theories causes it to differ functionally from the conspiracy mentality, even if these differences are generally subtle.…”
Section: Do the Two Types Of Scales Measure The Same Construct?mentioning
confidence: 99%
“…A meta-analysis of zero-order correlations has shown conspiracy mentality to be less strongly related to low cognitive ability (r = .20 for the BCTI, r = .09 for the CMQ; Stasielowicz, 2022). Furthermore, Pan et al (2023) observed that climate change denial was positively related to belief in conspiracy theories but negatively related to endorsement of conspiracy mentality statements. Taken together, these findings suggest that the greater empirical riskiness of belief in conspiracy theories causes it to differ functionally from the conspiracy mentality, even if these differences are generally subtle.…”
Section: Do the Two Types Of Scales Measure The Same Construct?mentioning
confidence: 99%
“…This would allow empirical exploration of the hypothesis that the latter distrust might be a heuristic aid to democratic processes by encouraging people to be suspicious of what powerful interests are doing and what they are being told (e.g., Briggs, 2004;Enders & Smallpage, 2018;Huntington, 1983;Sobo, 2021). Some promising divergences between the CMQ and measures such as the BCTI are indeed already being observed in meta-analysis (Stasielowicz, 2022), and in the small number of studies that run them both at the same time using covariance analysis (e.g., Pan et al, 2023; for review, see Trella et al, 2024, this issue). Toward these aims, informed by Nera's (2024, this issue) critique and our elaboration, we recommend that researchers:…”
Section: Conclusion and Recommendations For Researchersmentioning
confidence: 99%